From passive to critical consumption: The role of educational content in short videos to improve students' critical thinking skills - Aspar, Fathir; Refdinal, Refdinal; Erizon, Nelvi; Jasman, Jasman; Irzal, Irzal; A, Yufrizal (Jurnal Pendidikan Teknologi Kejuruan, 2025)
The engaging and personalized nature from short video makes it quickly popular, yet concerns persist about their potential to diminish critical thinking skills. This study investigates whether short videos with educational content can improve students' critical thinking skills. Using a quasi-experiment method, Thirty-three participants were divided into control and experimental groups, with critical thinking measured using the Holistic Critical Thinking Scoring Rubric (HCTSR) based on essay analysis in pretest and posttest. After administering educational short videos to the experimental group, the results showed that there was an increase in students' critical thinking skills, shown by the result of controlling the pretest variable through the ANCOVA test with a p-value of <0.001. The result highlights the potential of educational short videos as tools for fostering critical thinking by providing interventions which prioritize treatment fidelity through standardized protocols (SOPs) for content delivery, validating assessment tools, and structuring content design. Recommendations for future research include larger sample sizes, repeated data collection at strategic intervals, and rigorous validation of question complexity.